PENGARUH DISKON HARGA, GRATIS ONGKIR DAN VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN DI ONLINE SHOP (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS TRIBHUWANA TUNGGADEWI MALANG) - Awung, Irma Sartina; Indah, Sri; Putri, Sri Andika (Unitri Press, 2025)
The rapid development of technology has changed the way people live, as well as the lives of students. Online shop is one of the platforms to make it easier for consumers to shop 24 hours a day without having to face to face. Online stores implement several price discount strategies, free shipping to attract consumers. The purpose of this research is to understand how price discounts, free shipping, and viral marketing affect students' decisions to buy in online stores. The method used was quantitative with a sampling technique using purposive sampling. The total population in this study is 1484 students. To collect researchers, use a questionnaire distributed online through a google form in the Student Association group on the whatshapp application. 153 people were the researcher's sample for this study. According to the findings of the t-test study, the price discount variable has a significant value 0,003 0,05 and calculation values 3,004 t-table 1,97601. This shows that students' decision to buy from online retailers is somewhat influenced by the variable of price discounts. With t-count value 0,702 t-table 1,97601 and significant value 0,484 0,05, The free delivery variable has no influence on students' decision to buy at online retailers. With a value of sig. 0,000 0,05, and t-count 4,156 t-table 1,97601, Viral marketing variables are known to have an influence on students' online shopping decisions. Meanwhile, simultaneously the variables of discounts, free shipping and viral marketing have an effect on students' purchase decisions in online stores and the value of f-calculation 19,404 f table 2,67 and niliai significance of 0,000 0,05.